Can Rural E-Commerce Become the Adhesive Between Urban and Rural Areas in the Digital Age? - Wang, Xinyue (International Journal of Global Economics and Management, 2024)
The most difficult job still rests in rural areas: promoting rural regeneration extensively and building a socialist modernized nation. The development of rural and agricultural regions must be given priority in the future, in addition to facilitating the transfer of urban and rural components and integrating urban and rural development. The Taobao village and Theil index provincial panel data from 31 Chinese provinces between 2014 and 2022 as the foundation for our investigation. Using a fixed effects model and multiple linear regression approach, the effects of expanding rural e-commerce on the income gap between urban and rural regions and the return of the rural population are explored. The findings demonstrate that e-commerce in rural areas expanding may raise the return on investment for rural populations while also reducing the difference in income between those living in cities and rural areas. Nonetheless, there remains a considerable disparity in wealth between the countryside and the cities in several of our nation’s provinces, and these inequalities vary greatly from year to year. The level of development of rural e-commerce varies significantly between different locations, with the general level of development falling between moderate and poor.